Multiple Signals of Coherence Relations - Debopam Das; Maite Taboada (Discours)
In this paper, we investigate the signalling of coherence relations when they are simultaneously indicated by more than one signal. In particular, we examine the co-occurrence of discourse markers and other relational signals when they are used together to mark a single relation. With the goal to identify the source of the usage of multiple signals, we postulate a two-fold hypothesis: the co-occurrence of discourse markers and other textual signals can result from the type of the discourse markers themselves, or it can be triggered by the semantics of the relations in question. We conduct a corpus study, examining instances of multiple signals (co-occurrence of discourse markers and other signals) in the RST Signalling Corpus (Das et al., 2015). We analyze discourse markers that appear as part of multiple signals and also relations that frequently employ multiple signals as their indicators. Our observations suggest that the signalling of relations by multiple signals is a complex phenomenon, since the co-occurrence of discourse markers and other textual signals appears to arise from multiple sources.